Fatty Pancreas: Disease or Finding? - Lucas de Lucena Simões e Silva; Matheus Santos de Sousa Fernandes; Eline Autran de Lima; José Tadeu Stefano; Claudia P. Oliveira; José Jukemura (Clinics, 2021)
Despite a growing number of investigative studies on pancreatic fat deposition, there remains no clear indication regarding the clinical relevance of fat infiltration in the pancreas, also called fatty pancreas (FP). An individual’s body weight is correlated with their pancreatic weight. Moreover, lipid infiltration causes disorders that compromise not only morphology but also metabolic functions. Fat infiltration leads to insulin resistance, type II diabetes mellitus, and pancreatic cancer; however, knowledge about pancreatic fat content and aspects related to the clinical profile remains unclear in the literature. The present review describes the current knowledge of FP, including its pathophysiology and clinical implications, as well as lifestyle changes in FP.